1982
DOI: 10.1021/bi00263a013
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-15 spin-lattice relaxation times of amino acids in Neurospora crassa as a probe of intracellular environment

Abstract: The nitrogen-15 spin-lattice relaxation time, T1, and the nuclear Overhauser enhancement (NOE) have been measured for intracellular glutamine, alanine, and arginine in intact Neurospora crassa mycelia to probe their various intracellular environments. The relaxations of 15N gamma of glutamine, 15N alpha of alanine, and 15N omega, omega ' of arginine in N. crassa were found, on the basis of their NOE values, to be predominantly the result of 15N-H dipolar relaxation. These relaxations are therefore related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 11 publications
1
42
0
Order By: Relevance
“…Chemical shifts are reported relative to "NH: at 0 ppm. Assignments of "N resonances were made by comparison with known spectra of amino acids and published data [2,3]. The assignments are additionally supported by protoncoupled "N-NMR spectra of the samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical shifts are reported relative to "NH: at 0 ppm. Assignments of "N resonances were made by comparison with known spectra of amino acids and published data [2,3]. The assignments are additionally supported by protoncoupled "N-NMR spectra of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…NMR spectroscopy is a useful technique for observing the flow of metabolites through pathways in vivo, as has been demonstrated by 13C-NMR studies of glycolysis and Krebs cycle in bacteria, fungi, and mammalian tissues [l]. The feasibility of observing intracellular ["Nlamino acids in intact cells of Brevibacterium lactofermenturn [2] and mycelia of Neurospora crassa [3] has recently been demonstrated by using highresolution "N-NMR. Despite these promising pioneering works, "N has not been used extensively as an NMR probe.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the internal pH of the N. crassa vacuole, observed in vivo with NMR, showed it to be an acidic compartment, pH 6.1, while the surrounding cytosol was neutral, pH 7.1 [81]. Less is known about the electrical gradient, but, in a few instances, measurements with microelectrodes have shown a slightly positive value (25-40 mV) for the interior of the vacuole relative to the cytosol (C.L.…”
Section: Functionmentioning
confidence: 99%
“…Direct isolation of vacuoles (27) has shown that less than 1% lies in this organelle, and only about 6% is present in other organelles. Similarly, in vivo experiments using "5N NMR have demonstrated that the bulk of the alanine lies in an environment different in both pH (20) and viscosity (15) from that of vacuolar amino acids such as arginine and histidine. However, by the time the alanine pool was restored to its initial level (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…4), the '3C-enriched pool was 50% of the cellular alanine. That this degree of compartmentalization of the alanine pool preexisted on SM appears unlikely (15,20,27), suggesting that the sequestration increased as part of the adaptation process. Given that the unenriched alanine pool and gluconeogenesis were cytosolic and that there was evidence for a TCA cycle contribution to the latter in the '3C enrichments of C-3,3' and C-4,4' of trehalose (Fig.…”
Section: Resultsmentioning
confidence: 99%